2018
DOI: 10.1016/j.jhsa.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Corrective Osteotomy for Malunited Distal Diaphyseal Radius Fractures in Children and Adolescents

Abstract: Therapeutic V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Since the spread of computer-aided planning and the introduction of PSIs in the last two decades, many different options have become viable to improve surgical accuracy and final outcome [ 1 , 4 , 21 , 22 , 23 , 24 , 25 ]. Technology has made it easier to achieve correction with a single oblique osteotomy, which allows correction of both the angular and rotational deformities, preserving bone length [ 4 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the spread of computer-aided planning and the introduction of PSIs in the last two decades, many different options have become viable to improve surgical accuracy and final outcome [ 1 , 4 , 21 , 22 , 23 , 24 , 25 ]. Technology has made it easier to achieve correction with a single oblique osteotomy, which allows correction of both the angular and rotational deformities, preserving bone length [ 4 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A step-by-step correction during growth must be expected. Alternatives to treatment with an external fixator should therefore be considered, as this is a lengthy treatment with added complications ( 21 , 27 , 28 ). In the older child one can consider ulnar shortening combined with epiphysiodesis if radial alignment is fine.…”
Section: Discussionmentioning
confidence: 99%
“…Miyake et al [7] included 20 patients with a forearm malunion and found an improvement in angular deformity and an improvement in the mean arc of forearm motion. Kataoka et al [14] investigated the use of computer-planning for the correction of malunited diaphyseal forearm fractures in four patients and found an improvement in angular deformity on X-ray, range of forearm rotation, and grip strength. These studies demonstrate that the use of 3D planning and printing of patient-specific guides helps surgeons to precisely perform corrective osteotomies of complex malunited fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of 3D preoperative planning and printing of patient-specific guides has significantly improved the interpretation of complex fractures. Several studies have shown that the correction of malunited forearm fractures can be precisely planned and performed using 3D analyses and printing of guides, which subsequently resulted in improved functional outcomes [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%